Improving Students' Critical Thinking Skills Using the Problem-Based Learning Model Assisted by Virtual Laboratories - Ramdinawati Syam, Yulia; Surti Kurniasih; Rita Retnowati (Universitas Pendidikan Ganesha, 2024)
Students' critical thinking skills currently are in the low category. It causes the need for innovation in learning methods and models that can improve students' thinking skills. This research aims to determine the improvement of students' critical thinking skills through the problem-based learning (PBL) learning model assisted by a virtual laboratory in the Biology learning process. This research uses a pre-experimental method with a one-group pretest post-test design. The research subjects consisted of 30 eleventh-grade high school students. Data collection methods include observation, critical thinking skills essay tests, and student response questionnaires. Data collection instruments use questionnaires and test questions. Test the empirical validity of the instrument using Pearson product-moment correlation in SPSS and Cronbach's Alpha to test its reliability. Data analysis uses the N-Gain Test for each indicator of critical thinking skills. The N-Gain test results show that applying the PBL learning model assisted by a virtual laboratory significantly increases the average critical thinking skills in the high category. Thus, there has been an increase in students' critical thinking skills through the learning process using the PBL learning model assisted by a virtual laboratory.